1983
DOI: 10.1177/003072708301200106
|View full text |Cite
|
Sign up to set email alerts
|

Forest management and the Pine Processionary Moth

Abstract: Pine forests of the Mediterranean area are subject to very serious depredations by the caterpillar of the Pine Processionary Moth. Although there are suitable habitats in other parts of the world, the moth has so far remained within this region because of its poor power of dispersal. Traditional methods of containing it are unsatisfactory and better results are to be expected from measures designed to stabilise the population at an acceptable level rather than to eradicate it entirely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
14
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 7 publications
2
14
0
3
Order By: Relevance
“…-Lep., Thaumetopoeidae) is one of the most de structive insects of Pinus and Cedrus in the Middle East, North Africa and many south ern European countries, including Portugal. The urticant hairs of the late instar larvae provokes serious reactions in humans and other mammals (Lamy 1990, Oliveira et al 2003 but it is also responsible for significant economic damage due to severe defoliation (Buxton 1983, Devkota & Schmidt 1990, Kanat et al 2005. Defoliation removes both photosynthetic material and sites where chemicals such as growth hormones are pro duced, affecting many vital functions (Carus 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…-Lep., Thaumetopoeidae) is one of the most de structive insects of Pinus and Cedrus in the Middle East, North Africa and many south ern European countries, including Portugal. The urticant hairs of the late instar larvae provokes serious reactions in humans and other mammals (Lamy 1990, Oliveira et al 2003 but it is also responsible for significant economic damage due to severe defoliation (Buxton 1983, Devkota & Schmidt 1990, Kanat et al 2005. Defoliation removes both photosynthetic material and sites where chemicals such as growth hormones are pro duced, affecting many vital functions (Carus 2004).…”
Section: Introductionmentioning
confidence: 99%
“…-Lep., Thaumetopoeidae) is one of the most de structive insects of Pinus and Cedrus in the Middle East, North Africa and many south ern European countries, including Portugal. The urticant hairs of the late instar larvae provokes serious reactions in humans and other mammals (Lamy 1990, Oliveira et al 2003 but it is also responsible for significant economic damage due to severe defoliation (Buxton 1983, Devkota & Schmidt 1990, Kanat et al 2005 (1971) reported that T. pityocampa attack was responsible for an about 45% volume decrease over a 50 year period.The effect of insect action on trees can be studied using predictive models (Hogg 1999) which allow estimates of dendrometric va riables (e.g., height, volume, and biomass) and can be used for inventory techniques in production studies (Komiyama et al 2008, Sochackia et al 2007). However, the use of allometric models to estimate the impact of insects on forest dynamics is virtually un known.…”
mentioning
confidence: 99%
“…As P. radiata is more susceptible to T. pityocampa than many other pine species [26], [27], [28], we assumed that the damage function described above would provide a conservative estimate of damage. The damage function (Equation 1) was applied to the Ecoclimatic Index results for each 10′ climate station cell in New Zealand to create a polygon fishnet dataset of P.radiata potential proportional growth reduction.…”
Section: Methodsmentioning
confidence: 99%
“…[26], [27], [28]. Through time, defoliation appears to cycle [29] and this may be due to an unknown factor that reduces larval survival on plants that have suffered repeated defoliation [30].…”
Section: Introductionmentioning
confidence: 99%
“…Emergence may take up to a year, depending on climatic conditions. This insect is responsible for significant economic damage due to severe defoliation (Buxton, 1983;Devkota and Schmidt, 1990;Kanat et al, 2005;Arnaldo et al, 2010), while the urticant hairs of the late instar larvae provokes serious reactions in humans and other mammals (Lamy, 1990;Oliveira et al, 2003).…”
Section: Introductionmentioning
confidence: 99%